IL‐33 promotes the induction of immunoglobulin production after inhalation of house dust mite extract in mice. Issue 5 (3rd March 2015) - Canbaz, D.; Utsch, L.; Logiantara, A.; van Ree, R.; van Rijt, L. S.
Abstract Background The initial immune response to house dust mite (HDM) is orchestrated by an interplay between epithelial cells (ECs) and dendritic cells (DCs). Innate cytokines released by HDM‐exposed ECs activate airway DCs and effector inflammatory cells, which together induce a HDM‐specific Th2 cell response. Here, we investigate the respective roles of DCs and IL‐33 in sensitization to HDM. Method Balb/c mice were exposed via the airways to different HDM extracts, differing in at least endotoxin levels [Lotox (LT) and HiTox (HT)]. Alternatively, HDM‐pulsed DCs in the presence or absence of additional LT‐HDM, or administration of LT‐HDM plus recombinant IL‐33, were intratracheally (i.t.) administered to induce allergic airway inflammation. Eosinophil recruitment, cytokine production, serum immunoglobulins, and airway histology were analyzed. Results Direct exposure of airways with HT‐HDM induced an eosinophilic airway inflammation, Th2 cytokine production, and an increase in total IgE and HDM IgG1, while LT‐HDM was not able to do so. In contrast, i.t. instillation of LT‐HDM‐pulsed DCs induced a similar airway inflammation, mucus production, and cytokine production, but IgE or HDM IgG1 was not induced. Administration of HDM‐pulsed DCs together with LT‐HDM, to supply B cells with unprocessed antigen, was not sufficient to induce antibody production. Simultaneous administration of recombinant IL‐33 with LT‐HDM induced an antibody response, besides a cellular immune response. Conclusion These results demonstrate that HDM‐pulsed DCs were able to drive a Th2 response but that IL‐33 was needed to induce a humoral immune response to a single inhalational challenge to HDM.